Organising Levels of Organisation for Biology Education: A Systematic Review of Literature - Niklas Schneeweiß; Harald Gropengießer (MDPI AG, 2019)
Many authors suggest an explicit reflection on the levels of organisation, based on known difficulties related to understanding biological systems. Yet, there is no scientific consensus on the characteristics of biological levels and the quality of their relationships. This review intends to present the state of the current discussion in order to establish an educational argumentation as a basis for the development of learning environments and teaching experiments in biology education. For this purpose, we conducted a systematic literature review. Three databases (BIOSIS, ERIC, Fachportal-Pädagogik) were searched for literature on levels of organisation. The papers were analysed by means of a qualitative content analysis based on the following research questions: (1) Which levels of organisation do the authors name? (2) How do the authors describe the levels of organisation? (3) How do the authors describe the relationship between different levels of organisation? (4) How do the authors describe the challenges of these levels for biological education? (5) How do the authors describe the benefit of these levels for biological education? Based on the results, we propose a system of levels that features the concept of zooming-in and makes the relationships between the levels explicit.